Penyelesaian Perkara Tindak Pidana Penganiayaan Dengan Pelaku Anak Menurut Undang-Undang Nomor 11 Tahun 2012 - Indra Wijayanti; Elsa Rina Maya Toule; Sherly Adam (PAMALI: Pattimura Magister Law Review, 2021)
Introductioan: Cases of criminal abuse with child offenders, the form of settlement is a restorative justice approach through diversion, which is an initial step in the settlement process before proceeding to the next legal process.Purposes of the Research: This study aims to analyze and discuss the form of settlement of cases of criminal abuse with child offenders according to Law Number 11 of 2012.Methods of the Research: The type of research used in this research is Normative Juridical. Approach the problem using a statutory approach (statute approach), conceptual approach (conceptual approach) and a case approach (Case approach). Sources of legal materials include primary legal materials and secondary legal materials. The technique of collecting legal materials through documentation studies and analysis of legal materials uses qualitative analysis.Results of the Research: The research results show In if the settlement of a criminal case of persecution through diversion is successful in peace between the parties, the report will be withdrawn because there has been a mutual agreement in the settlement that has been carried out. Not all of these settlement processes with diversion can run smoothly and have succeeded in reaching a peace agreement between the parties. If in the event that the diversion process does not result in a peace agreement or the diversion agreement is not implemented, the juvenile criminal justice process will proceed to the Court and the settlement of cases of criminal abuse with child perpetrators is in accordance with Law No. 11 of 2012. However, in the settlement of cases of criminal abuse with child offenders there are still obstacles faced by law enforcement officials and the parties in litigation.